Associations of Partnership Quality and Father-to-Child Attachment During the Peripartum Period. A Prospective-Longitudinal Study in Expectant Fathers - Knappe, Susanne; Petzoldt, Johanna; Garthus-Niegel, Susan; Wittich, Julia; Puls, Hans-Christian; Huttarsch, Isabell; Martini, Julia (Frontiers in Psychiatry, 2021)
Background: During the transition to parenthood, a complex network of relationships unfolds between father, mother and the child. Expectant parents begin bonding with their unborn child, with this antenatal process supposedly being predictive for later postnatal attachment and child mental health. At the same time, couples may experience a change in partnership quality. While the majority of previous studies focused on associations between psychopathology, partnership quality and attachment from the perspective of mothers, the changes in partnership quality and attachment from the perspective of fathers has gained far less attention. Methods: Data were derived from the Maternal Anxiety and it's Relation to Infants' Development (MARI) study. N=109 expectant fathers were recruited during mid-pregnancy (22 to 26 week of gestation). Lifetime anxiety and depressive disorders (DSM-IV) were assessed with a standardized diagnostic interview (CIDI). Paternal partnership characteristics and father-to-child attachments were assessed using standardized questionnaires at the second trimester, 10 days after delivery and 4 months after delivery in N=76 fathers. Analyses were based on bivariate, robust and multivariate regression analyses. Results: Fathers did not report an overall decrease in partnership quality during the peripartum period. However, fathers with comorbid anxiety and depressive disorders reported lower partnership satisfaction at postpartum, as compared to unaffected fathers. Fathers with pure depressive disorders reported lower intensity of antenatal attachment. Paternal antenatal partnership quality was positively associated with antenatal father-to-child attachment. Furthermore, antenatal father-to-child attachment, as well as ante- and postnatal partnership quality in fathers, were positively related to postnatal father-to-child attachment. Conclusions: Antenatal father-to-child-attachment and paternal partnership quality appear to be promising targets for the prevention of postnatal attachment problems in fathers. The associations between partnership quality and attachment to the child further support an interpersonal approach in perinatal research, treatment and intervention, and may also feed into awareness programs that encourage expectant fathers to actively engage in relationships as early as during pregnancy – both with the mother and the unborn child.